Follow the sun! How investments in solar power plants in Sicily can generate high returns of investments and help to prevent global warming - Jan Christian Schinke (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2010)
Germany could have reached Kyoto protocol obligations earlier if German solar investments would be relocated to Sicily. Additional benefits of emission savings and energy production should rise up to 72%. Nevertheless German solar power plants 2008 counted for 20 % of the financial benefits through support mechanisms EEG for renewable energies while the share at produced green energy was not more than 4,8%. The system seems absurd from an economical view, but is adopted in many other countries. Firstly, the paper will analyse general economic theories to underline the importance of financial supports for renewable energies and why policy maker can justify the subsidies for selected technologies through social costs effected by carbon exhaust. Secondly, place does matter and physics are the limit: the following chosen approach for expected final yield shrinks the additional benefits of the theoretical relocated south solar investments to +37%. Thirdly, the conclusions give political recommendations for the design of further subsidies of solar energies in Europe.
Keywords: Q42; Q48; Q54; L51; H23; 330; Photovoltaics; Renewable Energies; Feed in Tariffs; Carbon Exhausts; Global Warming; European Energy Policies; Förderung regenerativer Energien; Sonnenenergiepolitik; Direktinvestition; Deutsch; Wirtschaftlichkeit; Klimaschutz; Sizilien; Deutschland